Casearia sylvestris Swartz Extract Release Using Natural Rubber Latex Biomembranes as Carrier - Borges, Felipe Azevedo; Trecco, Alberto; Miranda, Matheus Carlos Romeiro; Perri, Elaíse G.; Santos, André Gonzaga dos; Herculano, Rondinelli Donizetti [UNESP]; Barros, Natan Roberto (Sciencedomain International, 2014)
The Natural Rubber Latex (NRL) from Hevea brasiliensis has shown promise in biomedical applications due to its low cost, easy handling, mechanical properties and biocompatibility, being used for bone regeneration and wound healing due to its natural stimulus to angiogenesis. The aim of this work was to incorporate Casearia sylvestris Sw. extract in NRL biomembranes and study its release behavior. The complex membrane-extract has as object of study a new approach of using C. sylvestris extract in the treatment of wounds, for possessing antiseptic activity, anti-inflammatory and analgesic properties. The C. sylvestris species (Salicaceae), popularly known as "guaçatonga", presents great distribution and is used in folk medicine as antiulcer, wound healing, anti-snake venom, properties which have been proven and related to clerodane diterpenes (casearins A-X). The release rate of C. sylvestris compounds from extract-membrane complex was monitored and analyzed using the method of optical spectroscopy (UV-VIS). The release varied with temperature ranging from 14 to 33 days, releasing more than 90%, with an interesting and promising biomedical application, such as wound healing and burns.
Keywords: Casearia sylvestris Swartz; Latex membrane; natural rubber